INFORMATION PROCESSING DEVICE, INFORMATION PROCESSING TERMINAL, DISTRIBUTION METHOD, AND TIME SYNCHRONIZATION METHOD - OTSUKA Masahiro; TANAKA Nobuyuki; IZUMI Akihiko (2022)
This technology relates to an information processing device, an information processing terminal, a distribution method, and a time synchronization method which make it possible to easily set an appropriate time synchronization method for each of multiple devices. An information processing device, according to one aspect of this technology, distributes, in response to a request from a client device, information representing a time synchronization strategy set as a method for time synchronization between client devices forming the same group. This technology is applicable to a server connected to a network. Cette technologie concerne un dispositif de traitement d'informations, un terminal de traitement d'informations, un procédé de distribution et un procédé de synchronisation temporelle qui permettent de régler facilement un procédé de synchronisation temporelle approprié pour chacun de multiples dispositifs. Un dispositif de traitement d'informations, selon un aspect de cette technologie, distribue, en réponse à une requête provenant d'un dispositif client, des informations représentant une stratégie de synchronisation temporelle définie en tant que procédé de synchronisation temporelle entre des dispositifs clients formant le même groupe. Cette technologie est applicable à un serveur connecté à un réseau. 本技術は、適切な時刻同期の方法をそれぞれの機器に対して容易に設定することができるようにする情報処理装置、情報処理端末、配信方法、時刻同期方法に関する。 本技術の一側面の情報処理装置は、クライアント機器からの要求に応じて、同じグループを形成するクライアント機器間の時刻同期の方法として設計された時刻同期戦略を表す情報を配信する。本技術は、ネットワークに接続されるサーバに適用することができる。